Roald Amundsen’s sled dogs : the sledge dogs who helped discover the South Pole - Tahan, Mary R (Springer, 2019)
Keywords: Antarktis; Roald Amundsen; Sydpolsekspedisjonen; oppdagelsesreiser; sledehunder; trekkhunder

Kapten Roald Amundsen: I vargskinnspäls och textil. Blir först på Sydpolen - Norén, Karl-Gunnar (Polarfararnas kläder : på liv och död, 2018)
Keywords: Antarktis; Roald Amundsen; Sydpolsekspedisjonen; oppdagelsesreiser; polarekspedisjoner; utstyr

Lessons from the Arctic : how Roald Amundsen won the race to the South Pole - Kløver, Geir Olav (Fram Museum, 2017)
Keywords: Antarktis; Belgica ekspedisjon; Sydpolsekspedisjonen; oppdagelsesreiser; polarhistorie

Naturen 1916 Roald Amundsens sydpolsfærd og dens videnskabelige resultater (Naturen, 2016)
Efterat kaptein James Ross i 1841 hadde opdaget det sydpolare eller antarktiske fastland og den store isbarriere under sin seilas i det hav som efter ham har faat navn av Ross-Havet, blev den øvrige del av dette fastland fremdeles ukjendt indtil 1898. Fra dette aar av har en række ekspeditioner med større og mindre held forsøkt at finde beliggenheten av det antarktiske fastlands kyster, og av disse har nogen opnaadd at trænge ind i det indre, endog like til sydpolen. Imidlertid er der endnu store strækninger hvor havisen har stængt seilasen og gjort det umulig at naa ind til det faste land.
Keywords: Antarktis; Roald Amundsen; Sydpolsekspedisjonen; historie; oppdagelsesreiser; vitenskap

Den nyttige taperen - Scotts plass i norske nyhetsmediers fortellinger om erobringen av Sørpolen - Alnæs, Jørgen; Simonsen, Anne Hege (Norsk medietidsskrift, 2016)
Hundre år etter at Roald Amundsen nådde Sørpolen, ble han behørig feiret både av det offisielle Norge og av norske nyhetsmedier. Robert F. Scott, som nådde polen om lag en måned seinere, var en del av omtalen. Han fikk rollen som motstander og taper, og slik ble han en nyttig brikke når forestillingene om Norge som en rettmessig stormakt i Antarktis skulle etableres. Det er imidlertid mange måter å framstille Scott på, og norske aviser har ikke alltid hatt det samme synet på ham.
Publisher: Universitetsforlaget
Keywords: Antarktis; Roald Amundsen; Robert Falcon Scott; Sydpolsekspedisjonen; ekspedisjoner; historie; kappløpet; mediefortelling; oppdagelsesreiser

On Roald Amundsen’s scientific achievements - Blix, Arnoldus Schytte (Polar Research, 2016)
This paper describes the significant direct and indirect contributions to science made by the Norwegian polar explorer Roald Amundsen in the period 1897–1924. It documents that his expeditions through the North-west Passage (1903–06) with Gjøa, to the South Pole (1910–12) with Fram and through the North-east Passage (1918–1920) and the Chukchi and East Siberian seas (1921–25) with Maud yielded vast amounts of published scientific material on meteorology, terrestrial magnetism, geology, palaeontology, oceanography, ethnography, zoology and botany, which, though celebrated at the time, have since received scant recognition in more recent assessments of Amundsen’s achievements. Keywords: Fridtjof Nansen; polar exploration; South Pole; North-west Passage; North-east Passage; H.U. Sverdrup.
Keywords: Antarktis; Roald Amundsen; Sydpolsekspedisjonen; ekspedisjoner; forskning; geologi; meteorologi; oseanografi

The canine explorers – the sled dogs who helped Roald Amundsen reach the South Pole - Tahan, Mary R (Journal of Antarctic Affairs, 2016)
One hundred Greenland dogs were purchased by Roald Amundsen from the Royal Greenland Trading Company in September 1909 ostensibly for a North Pole expedition, but secretly to use to reach the South Pole. Amundsen considered the dogs “equipment”. He was a complicated character in a very different time. And he compulsively pursued his mission. His actions perhaps are seen differently from the 21st century perspective and in light of our evolving attitude toward animals, especially dogs. This paper presents the facts of what happened concerning the sled dogs, using Amundsen’s own statements in his books, diaries, and letters, as well as the expedition members’ journal entries and personal letters. It focuses on the dogs who made Amundsen’s exploration possible, and who helped humankind discover the final undiscovered part of our world. Amundsen began his Norwegian expedition with 97 sturdy canine souls, who were taken on board the Fram near the coast of Kristiansand in August 1910. Through births and deaths on the ship during their five-month journey south, the dogs’ number swelled to 116 upon arrival in Antarctica. Adults and puppies alike withstood the roller-coaster ride of the Fram on the ocean waters, the heat of the tropics near the equator, and the freezing winter of Antarctica. Taking into account the birth of puppies on the ship and at their Antarctic home Framheim, the actual number of dogs involved in this significant moment in history doubles to over two hundred. But, after initially nurturing and protecting the dogs, Amundsen proceeded to cull them throughout the expedition, slaughtering those he deemed unnecessary or weak, and destroying those who had served their purpose. Amundsen began his South Pole trek in October 1911 with 52 brave canines, and returned with 11, as a result of unnatural, forced attrition. The dogs were nearly starved; at times when they were fed, it was the flesh of their fallen comrades they were given to line their empty stomachs. And yet the dogs all performed their roles brilliantly, even when death was their reward. The sled dogs were the heart and power of the South Pole expedition. The intent of this article is to shine a light on the dogs’ population, accomplishments, and sacrifices, and to give them their due recognition and place in history.
Publisher: Agenda Antártica. Antarctic and Southern Ocean Coalition (ASOC)
Keywords: Antarktis; Roald Amundsen; Sydpolsekspedisjonen; oppdagelsesreiser; sledehunder; trekkhunder

The great white silence : den offisielle filmen om Robert Falcon Scotts sydpolekspedisjon og en vurdering av ekspedisjonen - Lund, Vidar (Maritimt Magasin Historie, 2015)
Publisher: Commentum Forlag Place: Oslo
Keywords: Antarktis; Robert Falcon Scott; Sydpolsekspedisjonen; oppdagelsesreiser

"Toffe karer spiser pemmikan" - Lundin, Kjell (Pemmikan : en hårdkokt historia, 2015)
Keywords: Antarktis; Roald Amundsen; Sydpolsekspedisjonen; ernæring; mat

Leadership lessons from the race to the South Pole : why Amundsen lived and Scott died - O'Connell, Fergus (Praeger, 2015)
A project management expert identifies methods for running any project successfully based on lessons learned from the exploits of two storied explorers.
Keywords: Antarktis; Nordmenn; Roald Amundsen; Sydpolsekspedisjonen; ekspedisjoner; oppdagelsesreiser

The significance of petroleum for the South Pole expeditions 1910-1912 - Skarung, Per (The Fram Museum, 2015)
"Inclement weather and lack of fuel was the cause of their deaths".
Keywords: Antarktis; Roald Amundsen; Robert Falcon Scott; Sydpolsekspedisjonen; polarhistorie

Hiihtovaellus etelänavalle : eräretki Roald Amundsenin jäljissä - Aasheim, Stein P; Paarma, Susanna (Gummerus, 2014)
Keywords: Antarktis; Sydpolen; Sydpolsekspedisjonen; ekspedisjoner; reiser; reiseskildringer; skisport

The Third Expedition, 1910-1912: Antarctica and the Southern Ocean - Johnson, Charles W (Ice ship : the epic voyages of the polar adventurer Fram, 2014)
Keywords: Antarktis; Fram (skip); Roald Amundsen; Sydpolsekspedisjonen; Sørpolen; ekspedisjoner; oppdagelsesreiser; polarekspedisjoner

Tryggve Gran : is, luft og krig - Simonsen, Anne Hege (Cappelen Damm, 2013)
Keywords: Antarktis; Sydpolen; Sydpolsekspedisjonen; biografier; ekspedisjoner; oppdagelsesreiser; polarområdene

I Roald Amundsens skispor : kappløpet til Sørpolen - 100 år etter - Aasheim, Stein P (Cappelen Damm, 2012)
Keywords: Antarktis; Sydpolen; Sydpolsekspedisjonen; ekspedisjoner; reiser; reiseskildringer; skisport

Roald Amundsen: Forsker eller grobian? - Blix, Arnoldus Schytte (Nordisk tidskrift för vetenskap, konst och industri, 2012)
Roald Amundsens (1872-1928) liv og bedrifter er fremstilt i en rekke biografier, men det er oppdageren og eventyreren som blir tillagt mest vekt, mens vitenskapsmannen og forskeren tidvis underkjennes. Professor i arktisk biologi ved Universitetet i Tromsø, Arnoldus Schytte Blix, er kritisk til mye av det biografiske arbeidet som er gjort, og mener det er et åpent spørsmål om kontorhistorikere og journalister har noen reell mulighet til fullt ut å forstå Roald Amundsens situasjon og reaksjoner. Artikkelen er basert på et foredrag med en rekke illustrasjoner i Det Norske Videnskabs-Akademi, 17. november 2011.
Publisher: Föreningen Norden Place: Stockholm
Keywords: Antarktis; Roald Amundsen; Sydpolsekspedisjonen; biografier; oppdagelsesreiser

Norges ti viktigste polarekspedisjoner - Jaklin, Asbjørn; Jølle, Harald Dag (Norsk Polarinstitutt, 2012)
Publication Title: Norsk polarinstitutt. Rapportserie
Keywords: Antarktis; Carl Anton Larsen; Maudheim; NSBX 1949-52; Norge; Norsk-britisk-svenske antarktisekspedisjon; Roald Amundsen; Sydpolsekspedisjonen; polarekspedisjoner; polarforskning; polarområdene

Til Sydpolen - 100 år etter - Johansen, Asle T; Grindhaug, Gaute; Berg, Agnar (Fri flyt, 2012)
Keywords: Antarktis; Sydpolen; Sydpolsekspedisjonen; ekspedisjoner; reiser; reiseskildringer; skisport

Review of Race for the South Pole: the expedition diaries of Scott and Amundsen, by Roland Huntford - Jølle, Harald Dag (Polar Research, 2012)
Roland Huntford is the grand old man among polar historians. After his classic Scott and Amundsen in 1979 (later editions were retitled, The last place on Earth), he wrote a series of books on Norwegian and British polar heroes as well as a thorough study of the history of skiing (2006). Huntford challenged the British admiration of Robert Falcon Scott’s scientific programme and great courage*and insisted that Roald Amundsen’s expedition was far better prepared and carried out. Huntford’s scathing criticism of Scott’s fatal choices and lack of competence dared to assault this cherished British polar icon in a manner that would be unthinkable for Norwegian authors.
Keywords: Antarktis; Roald Amundsen; Robert Falcon Scott; Sydpolen; Sydpolsekspedisjonen; Sørpolen; bokanmeldelser; dagbøker; kappløpet; polarhistorie; polarområdene

The South Pole expedition of Roald Amundsen: how did he prepare for the expedition and what do his crewmembers' diaries tell us about it? / Geir O. Kløver. - Kløver, Geir Olav (Nimrod : the Journal of the Ernest Shackleton Autumn School, 2012)
Describes Amundsen's experience on de Gerlache's 1897-99 Belgica Antarctic expedition, scientific interests, lessons learned on his 1903-06 Gjøa Northwest Passage expedition, and experience on 1910-12 Fram Antarctic expedition. Gives details of crew members on Antarctic expedition with account of their diaries. Author is director of Fram Museum and editor of South Pole diaries of Amundsen and fourteen of his crew members.
Keywords: Antarktis; Belgica ekspedisjon; Sydpolsekspedisjonen; dagbøker; polarhistorie

Of reindeer, ponies and automobiles : Roald Amundsen and the Norwegian bid for the South Pole - Turney, Chris (1912 : the year the world discovered Antarctica, 2012)
Keywords: Antarktis; Sydpolsekspedisjonen; oppdagelsesreiser; polarhistorie

Sydpolsekspedisjonen 1910-1912 - Bjaaland, Olav (Frammuseet, 2011)
Publication Title: Frammuseet presenterer
Keywords: Antarktis; Fram (skip); Sydpolen; Sydpolsekspedisjonen; dagbøker; oppdagelsesreiser; polarområdene

Sydpolsekspedisjonen 1910-1912 - Gjertsen, Hjalmar Fredrik (Frammuseet, 2011)
Publication Title: Frammuseet presenterer
Keywords: Antarktis; Fram (skip); Sydpolen; Sydpolsekspedisjonen; dagbøker; oppdagelsesreiser; polarområdene

Sydpolsekspedisjonen 1910-1912 - Hassel, Sverre (Frammuseet, 2011)
Publication Title: Frammuseet presenterer
Keywords: Antarktis; Fram (skip); Sydpolen; Sydpolsekspedisjonen; dagbøker; oppdagelsesreiser; polarområdene

Sydpolsekspedisjonen 1910-1912 - Johansen, Hjalmar (Frammuseet, 2011)
Publication Title: Frammuseet presenterer
Keywords: Antarktis; Fram (skip); Sydpolen; Sydpolsekspedisjonen; dagbøker; oppdagelsesreiser; polarområdene

Das Eis und der Tod : Scott, Amundsen und das Drama am Südpol - Jostmann, Christian (Beck, 2011)
Keywords: Antarktis; Roald Amundsen; Robert Falcon Scott; Sydpolen; Sydpolsekspedisjonen; dagbøker; ekspedisjoner; historie; oppdagelsesreiser; polarområdene

Der Wettlauf zum Südpol : das grösste Abenteuer der Geschichte - Knopp, Guido; Sporn, Mario; Schnier, Marten (Bertelsmann, 2011)
Keywords: Antarktis; Roald Amundsen; Robert Falcon Scott; Sydpolen; Sydpolsekspedisjonen; dagbøker; ekspedisjoner; historie; oppdagelsesreiser; polarområdene

Bildeberetninger. Mediebegivenheter. Polprospekter - Lund, Harald Østgaard; Berg, Siv Frøydis (Norske polarheltbilder : 1888-1928, 2011)
Keywords: Antarktis; Nordmenn; Roald Amundsen; Sydpolsekspedisjonen; fotografi; fotohistorie; kulturhistorie; polarekspedisjoner; polarområdene; polfarere

Race to the end : Scott, Amundsen and the South Pole - MacPhee, Ross D E (The Natural History Museum, 2011)
Keywords: Antarktis; Roald Amundsen; Robert Falcon Scott; Sydpolen; Sydpolsekspedisjonen; dagbøker; ekspedisjoner; historie; oppdagelsesreiser; polarområdene

Sydpolsekspedisjonen 1910-1914 - Nilsen, Thorvald (Frammuseet, 2011)
Publication Title: Frammuseet presenterer
Keywords: Antarktis; Fram (skip); Sydpolen; Sydpolsekspedisjonen; dagbøker; oppdagelsesreiser; oseanografi; polarområdene

Le tombeau des glaces : duel mortel pour le pôle - Pierre, Marc (Dorval, 2011)
Publication Title: Collection Grandes aventures polaires
Keywords: Antarktis; Roald Amundsen; Robert Falcon Scott; Sydpolen; Sydpolsekspedisjonen; dagbøker; ekspedisjoner; historie; oppdagelsesreiser; polarområdene

Sydpolsekspedisjonen 1910-1912 - Prestrud, Kristian (Frammuseet, 2011)
Publication Title: Frammuseet presenterer
Keywords: Antarktis; Fram (skip); Sydpolen; Sydpolsekspedisjonen; dagbøker; oppdagelsesreiser; polarområdene

Sydpolsekspedisjonen 1910-1914 - Schröer, Adolf Hermann; Hansen, Ludvig; Rønne, Martin; Hanssen, Helmer; Kutschin, Aleksandr; Wisting, Oscar; Stubberud, Jørgen; Doxrud, Christian; Stubberud, Jørgen; Hansen, Ludvig; Rønne, Martin (Frammuseet, 2011)
Publication Title: Frammuseet presenterer
Keywords: Antarktis; Fram (skip); Sydpolen; Sydpolsekspedisjonen; dagbøker; oppdagelsesreiser; polarområdene

Sydpolsekspedisjonen 1910-1912 - Amundsen, Roald (Frammuseet, 2010)
Publication Title: Frammuseet presenterer
Keywords: Antarktis; Fram (skip); Sydpolen; Sydpolsekspedisjonen; dagbøker; oppdagelsesreiser; polarområdene

The South Pole expedition 1910-1912 - Amundsen, Roald (Frammuseet, 2010)
Publication Title: Frammuseet presenterer
Keywords: Antarktis; Fram (skip); Roald Amundsen; Sydpolen; Sydpolsekspedisjonen; dagbøker; oppdagelsesreiser; polarområdene

Roald Amundsens sydpolsferd (1910-1912) = Roald Amundsen's South Pole expedition (1910-1912) - Amundsen, Roald; Diesen, Jan Anders; Lund, Harald Østgaard (Norsk filminstitutt, 2010)
Publication Title: Roald Amundsen's South Pole expedition (1910-1912) Place: Oslo
Keywords: Antarktis; Fram (skip); Norge; Sydpolen; Sydpolsekspedisjonen; dokumentarfilmer; ekspedisjonsfilmer; oppdagelsesreiser; polarområdene

Race for the South Pole : the expedition diaries of Scott and Amundsen - Amundsen, Roald; Scott, Robert Falcon; Bjaaland, Olav; Huntford, Roland (Continuum, 2010)
Keywords: Antarktis; Roald Amundsen; Robert Falcon Scott; Sydpolen; Sydpolsekspedisjonen; dagbøker; ekspedisjoner; historie; kjeldeskrift; oppdagelsesreiser; polarområdene; polferder

Roald Amundsen: Conqueror of the South Pole - Thyvold, Hans Olav (Font forl., 2010)
ROALD AMUNDSEN (1872-1928), norsk oppdager, polfarer og nasjonalhelt. Det første mennesket som fant og seilte gjennom Nordvestpassasjen, og førstemann til å sette fot på Sydpolen. Norges nasjonalarv er en serie gjennomillustrerte bøker som presenterer våre viktigste og mest kjente nasjonale ikoner. De enkeltstående bøkene tar for seg betydelige skikkelser innenfor kunst og litteratur, vitenskap, idrett og samfunnsliv, men også landets mange naturperler, samt sentrale historiske epoker og kulturuttrykk. Hver for seg gir bøkene en oppdatert innføring for lesere som vil gjøre seg bedre kjent med et gitt tema.
Publication Title: Norwegian Heritage
Keywords: Antarktis; Sydpolsekspedisjonen; oppdagelsesreiser; polarhistorie

Roald Amundsen: Conqueror of the South Pole - Thyvold, Hans Olav; Cowlishaw, J Basil (Font forl., 2010)
ROALD AMUNDSEN (1872-1928), a Norwegian polar explorer and national hero. The first man to find and sail through the North-West Passage, and the first to set foot on the South Pole. NORWEGIAN HERITAGE is a series of illustrated books about our most important and best-known national icons. The respective titles introduce major personalities from the worlds of art and literature, science and sports, but also the many natural wonders of the country, as well as significant historical periods and cultural expressions. Each book offers an updated introduction to readers who wish to familiarize themselves with a given subject.
Publication Title: Norwegian Heritage
Keywords: Antarktis; Sydpolsekspedisjonen; oppdagelsesreiser; polarhistorie